Community Assistance in Utilizing Sharia-Based Digital Banking - Nugroho, Anton Priyo; Asfahani, Asfahani; Sugiarto, Fitrah; HS, Sufyati; Setiono, Agus; Sain, Zohaib Hassan (LP2M INSURI Ponorogo, 2023)
As one of the industries engaged in the business and financial sector, banks are certainly required to keep abreast of developments by advances in technology and information. The application of digitalization in the banking industry, especially Sharia Banking, is expected to create speed, convenience, flexibility, and convenience in non-cash transactions in society. This service activity aims to educate the public regarding the benefits and advantages of Sharia Digital Banking products and non-cash transactions. The participatory community empowerment method uses the Participatory Rural Appraisal (PRA) model. As a result of this activity, the public will receive new and accurate information on the use of Digital Banking products and be careful in non-cash transactions to avoid various financial crimes and increase public perception and knowledge of the development of Islamic Financial Literacy.